2010
DOI: 10.1016/j.juro.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless Percutaneous Nephrolithotomy—The New Standard of Care?

Abstract: Tubeless percutaneous nephrolithotomy appears to be safe and efficacious in uneventful procedures, in children, in obese patients, in simultaneous bilateral procedures, in supracostal access and in renal units with coexisting anatomical anomalies. Nephrostomy tube placement should still be considered in certain cases such as those with more than 2 nephrostomy access tracts, those necessitating a second look and those with intraoperative complications such as significant bleeding or collecting system perforatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 50 publications
1
53
0
3
Order By: Relevance
“…Zilberman et al reviewed the papers about tubeless PCNL. They reported similar results with tubeless PCNL compared to standard PCNL (6). With this approach, the target is to achieve less hospital days, less pain scores, less analgesics, faster return to normal activities and lower costs.…”
Section: Commentsmentioning
confidence: 76%
“…Zilberman et al reviewed the papers about tubeless PCNL. They reported similar results with tubeless PCNL compared to standard PCNL (6). With this approach, the target is to achieve less hospital days, less pain scores, less analgesics, faster return to normal activities and lower costs.…”
Section: Commentsmentioning
confidence: 76%
“…Karami et al reported their 5-year experience with tubeless PCNL in 201 patients and indicated that it can be done safely in kidney stones larger than 2 cm as well as in staghorn stones (15). In a review article that was done by Zilberman et al it was shown that tubeless PCNL has some advantages such as less pain, less debilitation, less costs, and a quicker recovery in all patient groups including children and obese patients (16). Istanbulluoglu et al used an externalized ureteral catheter instead of double j stent in tubeless patients to reduce the morbidity caused by stents and to omit the requirement of cystoscopy for its removal (17).…”
Section: Discussionmentioning
confidence: 99%
“…Bir meta-analizde; çoklu akses yapılması, peroperatif aktif kanama gözlenmesi, belirgin toplayıcı sistem perforasyonu olması, intratorasik yaralanma ihtimali ve sekonder taş hastalarında nefrostomi tüpü konulmasını tavsiye edilmiştir. 9 Isac ve ark.nın çalışmasında tüm hastalarına tüplü PNL yapan bir cerrah ile tüm hastalarına tüpsüz PNL yapan başka bir cerrahin hastaları karşılaştırılmış ve gruplar arasında anlamlı farklılık gözlenmemiştir. Araştırmacılar sadece sekonder PNL yapılacak hastalarda tüp konulmasını önermişlerdir.…”
Section: Discussionunclassified